Effect of biorationals and Predatory Mites incontrolling the Two-Spotted Spider Mite (Tetranychus urticae L) on Eggplant field in the Greenhouse - Altantsetseg Zul; Siiriimaa Amarsaikhan; Oyungerel Janlav; Undarmaa Davaasambuu (Proceedings of the Mongolian Academy of Sciences)
The Two-Spotted Spider Mite (TSSM) is a prevalent mite pest found worldwide and is extensively distributed in Mongolian greenhouses. In this study, we conducted a field experiment using predatory mites and botanical pesticides on eggplants infested by TSSM. We observed promising results in terms of reducing pest populations and achieving overall improved outcomes. The experiment took place in a 120 sq.m. greenhouse located at the "Agropark" training-research center of the Mongolian University of Life Sciences.